2023
DOI: 10.1017/s002221512300035x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of inadvertently excised parathyroid glands during thyroid surgery and the link with post-surgical hypoparathyroidism

Abstract: Objectives To evaluate the incidence of inadvertent parathyroidectomy, identify risk factors, determine the location of inadvertently excised glands, review pathology reporting in inadvertent parathyroidectomy, and explore relationships between inadvertent parathyroidectomy and post-surgical hypoparathyroidism or hypocalcaemia. Methods A retrospective cohort study of 899 thyroidectomies between 2015 and 2020 was performed. Histopathology slides of patients who had an inadvertent parathyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…Likewise, it seemed like Graves’ disease and heavy specimen weight also were associated with an increased risk of permanent hypoPT, although not statistically significant. Other studies have found the same risk factors to be associated with an increased risk of hypoPT ( 1 , 2 , 13 , 16 , 18 , 37 ), and the lack of statistical significance in our study may be due to the small population size.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Likewise, it seemed like Graves’ disease and heavy specimen weight also were associated with an increased risk of permanent hypoPT, although not statistically significant. Other studies have found the same risk factors to be associated with an increased risk of hypoPT ( 1 , 2 , 13 , 16 , 18 , 37 ), and the lack of statistical significance in our study may be due to the small population size.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, the definition based on active vitamin D treatment reflects a more severe immediate hypoPT. Another potential explanation for the low rate of recovery following PG damage could be the low PG identification rate (61.2%) and the high proportions of patients experiencing PG autotransplantation (19.1%) and inadvertent PG excision (21.3%), as all these events are associated with an increased risk of hypoPT ( 1 , 2 , 18 , 37 ).…”
Section: Discussionmentioning
confidence: 99%